SARS-CoV-2 infection paralyzes cytotoxic and metabolic functions of the immune cells - Singh, Yogesh (Heliyon, 2021)
The SARS-CoV-2 virus is the causative agent of the global COVID-19 infectious disease outbreak, which can lead to acute respiratory distress syndrome (ARDS). However, it is still unclear how the virus interferes with immune cell and metabolic functions in the human body. In this study, we investigated the immune response in acute or convalescent COVID-19 patients. We characterized the peripheral blood mononuclear cells (PBMCs) using flow cytometry and found that CD8(+) T cells were significantly subsided in moderate COVID-19 and convalescent patients. Furthermore, characterization of CD8(+) T cells suggested that convalescent patients have significantly diminished expression of both perforin and granzyme A. Using (1)H-NMR spectroscopy, we characterized the metabolic status of their autologous PBMCs. We found that fructose, lactate and taurine levels were elevated in infected (mild and moderate) patients compared with control and convalescent patients. Glucose, glutamate, formate and acetate levels were attenuated in COVID-19 (mild and moderate) patients. In summary, our report suggests that SARS-CoV-2 infection leads to disrupted CD8(+) T cytotoxic functions and changes the overall metabolic functions of immune cells.